Cotyledon mckayi (Crassulaceae subfam. Kalanchooideae), a new cremnophytic species from the central Tugela River Basin of KwaZulu-Natal, South Africa - Crouch, Neil R.; Smith, Gideon F. (Phytotaxa, 2023)
A new Cotyledon species, C. mckayi is described from cliffs of the central Tugela River basin in KwaZulu-Natal province, South Africa. Although the flowers of this new species are superficially similar in terms of shape and size to those of C. nielsii, also from KwaZulu-Natal, C. mckayi is readily separable on both vegetative and reproductive characters, from this and all other taxa of Cotyledon that occur naturally in the province. A key to allow identification of fertile material of the Cotyledon species of KwaZulu-Natal is provided.